Selection of forward osmosis draw solutes for subsequent integration with anaerobic treatment to facilitate resource recovery from wastewater. (September 2015) - Ansari, Ashley J.; Hai, Faisal I.; Guo, Wenshan; Ngo, Hao H.; Price, William E.; Nghiem, Long D.
Highlights: An FO draw solute selection protocol is proposed for wastewater pre-concentration. Reverse solute flux of inorganic draw solutes may inhibit methane production. Ionic organic draw solutes are suitable for integrating FO with anaerobic treatment. BMP analysis is a reliable tool for assessing draw solute suitability. Abstract: Forward osmosis (FO) can be used to extract clean water and pre-concentrate municipal wastewater to make it amenable to anaerobic treatment. A protocol was developed to assess the suitability of FO draw solutes for pre-concentrating wastewater for potential integration with anaerobic treatment to facilitate resource recovery from wastewater. Draw solutes were evaluated in terms of their ability to induce osmotic pressure, water flux, and reverse solute flux. The compatibility of each draw solute with subsequent anaerobic treatment was assessed by biomethane potential analysis. The effect of each draw solute (at concentrations corresponding to the reverse solute flux at ten-fold pre-concentration of wastewater) on methane production was also evaluated. The results show that ionic organic draw solutes (e.g., sodium acetate) were most suitable for FO application and subsequent anaerobic treatment. On the other hand, the reverse solute flux of inorganic draw solutions could inhibit methane production from FO pre-concentrated wastewater.